2023
DOI: 10.3390/su15065210
|View full text |Cite
|
Sign up to set email alerts
|

Research on Restoration of Heavy Metal Contaminated Farmland Based on Restoration Ecological Compensation Mechanism

Abstract: In recent years, the development of industrialization has led to heavy metal pollution in many agricultural areas in China. The excessive heavy metals in farmland not only affect the normal growth of crops, but also do great harm to human health, which seriously restricts the development of ecology and food health in China. In order to improve the problem of heavy metal pollution in rural areas, the current situation of heavy metal pollution in rural areas is analyzed based on the innovative ecological compens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…Through ecological compensation, the environmental costs and ecological benefits generated by environmental treatment can be integrated into the traditional economic cost-benefit anal-ysis [21]. With the deepening of ecological compensation research, it continues to play an important role in biodiversity conservation [47], ecological restoration [48], and the coordination of regional environmental protection [49]. In addition, as an important tool for governments to coordinate cross-regional environmental governance [35], ecological compensation can effectively promote the regionalized cooperation of the government in environmental pollution management [31], thus forming a long-term mechanism of environmental governance with shared benefits and cooperation.…”
Section: Ecological Compensationmentioning
confidence: 99%
“…Through ecological compensation, the environmental costs and ecological benefits generated by environmental treatment can be integrated into the traditional economic cost-benefit anal-ysis [21]. With the deepening of ecological compensation research, it continues to play an important role in biodiversity conservation [47], ecological restoration [48], and the coordination of regional environmental protection [49]. In addition, as an important tool for governments to coordinate cross-regional environmental governance [35], ecological compensation can effectively promote the regionalized cooperation of the government in environmental pollution management [31], thus forming a long-term mechanism of environmental governance with shared benefits and cooperation.…”
Section: Ecological Compensationmentioning
confidence: 99%
“…Anthropogenic activities are important causes of heavy metal contamination in soil, such as mineral exploitation, agricultural activities, industrial activities, and transportation (Zhang et al, 2023). It has been reported that industrialization has led to heavy metal contamination in many of China's agricultural soils, and the excessive levels of heavy metals in agricultural land have seriously hampered the development of food security in China (Cai and Yang, 2023). In addition, compared to single-heavy metal contamination, multiple heavy metal contamination is more complex and poses a threat not only to human health but also to ecological functions (Qi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Forests contribute to global sustainable development [1,2], and questions on how to sustainably manage forests, restore degraded forest ecosystems, and increase forest area coverage globally are among the current major issues pursued by the international community [3][4][5]. Accurate evaluation of degraded forest ecosystems is the first step to solving these problems, and it is also the prerequisite and foundation for forest ecosystem restoration [6,7].…”
Section: Introductionmentioning
confidence: 99%